Discovering What Experiences Physical Therapist Students Identify as Learning Facilitators in Practical Laboratories - Francis-Coad, J.; Hill, Anne-Marie (2014)
Background and Purpose: Students who enroll in courses focusing on patient contact participate in practical laboratories, developing skills in a challenging, pre-clinical environment. Seeking a tutors perspective is beneficial during this process, as they are responsible for providing opportunities to engage and facilitate student learning. The purpose of this case report was to discover what type of experiences best-facilitated student learning in practical laboratory sessions. Case Description: Baccalaureate physical therapist (PT) students (n = 32) enrolled and participated in practical laboratories. An action research design utilized written student feedback, semi-structured interviews, and tutor observations to gain student perspective on what best-facilitated their learning. Data from these sources were coded, categorized, and concept mapped to reveal emergent themes. A final survey was then designed to represent the best learning facilitators identified from the student perspective. Outcomes: Students identified a variety of experiences that facilitated their learning. These facilitators included tutors, peers, and material resources. Students determined that the most efficient learning facilitator was receiving timely feedback from a tutor. During this time, students practiced required skills and behaviors, while tutors provided a structured peer checklist, clarifying their expectations through observation and feedback. Discussion: Action research outcomes suggest that when planning learning opportunities and developing resources, seeking comprehensive feedback from students can aid in successfully meeting their learning needs in practical laboratory settings.